Selapanan Bagi Masyarakat Jawa di Desa Batu Kecamatan Pitumpanua Kabupaten Wajo - Yulia Astuti; Mr. Jumadi (Rayhan Intermedia, 2023)
This research aims to find out about: 1) The process of determining the day for Javanese selapanan in Batu village, Pitumpanua sub-district, Wajo district; 2) The process of implementing selapanan in Batu village, Pitumpanua sub-district, Wajo district; 3) The meaning and function of selapanan for the Javanese community in Batu village, Pitumpanua subdistrict, Wajo district. In this research, researchers used descriptive qualitative research. The informants chosen were Javanese people who live in Batu village, Pitumpanua subdistrict, Wajo district. The researchers collected data by means of observation, interviews and documentation. The results of the research show that there are: 1) Selapanan traditions in Batu Village, Pitumpanua District, Wajo Regency, carried out when the baby reaches the age of 35 days or one month; 2) The process of implementing selapanan is carried out when the baby is 35 days old, inviting guests, preparation, distribution of bancaan; 3) The meaning of selapanan is as a celebration of the birth of a baby asking for protection, and hope for good growth, the function of selapanan is as a means of asking for prayers so that the baby will be given protection and smooth growth.